Properties of water-borne coating incorporate with nanoclay - Uyup, Mohd Khairun Anwar; Yusoh, Alia Syahirah; K., Tumirah; H., Hamdan; Md. Tahir, Paridah (IOP Publishing, 2018)
Water-borne coatings, as well as other coating options, are having advantages and disadvantages besides having different mechanical properties from those of the conventional solvent based coatings. A nanoparticle such as nanoclay (NC) has found its applicability in coatings to meet the mechanical requirements. In this study, a special focus has been given in order to improve the properties of water-borne coating using NC. The optimum percentage of NC mixed into water-borne coating was determined. The samples were prepared by dispersing 2 % of NC in water-borne coating. Both of it were mixed by using homogenizer for a certain duration using high speed rotation. The dispersion process was then repeated for 4 %, 6 %, 8 % and 10 % of NC loading. Whilst water-based coating without NC was used as control for comparison purposed. Effect of using NC on the mechanical properties of coatings on wood such as adhesion (ISO 2409:2007 (E) (BS EN 2007)), impact test (BS3962:Part6 1980 (BS 1980) scratch resistant (ISO 1518-1:2011 (BS EN 2011)) and abrasion (ASTM D 4060-14) were investigated. For adhesion properties, no detectable failure was observed for nanocoating with 2 %, 4 % and 6 % of NC. However, NC 8 % and NC 10 % showed a little detachment, indicating poorer adhesion quality for these samples. There are significant differences for impact and abrasion tests but insignificant for scratch test. It was found that the increasing amount of NC percentage would improve the mechanical properties of water based coating until a certain limit.